Big Data Analytics and Artificial Intelligence in Healthcare: Transforming Diagnostics, Treatment, and Disease Prevention. - Collins Nwannebuike Nwokedi,; Olakunle Saheed Soyege,; Obe Destiny Balogu,; Ashiata Yetunde Mustapha,; Busayo Olamide Tomoh,; Akachukwu Obianuju Mbata,; Dorothy Ruth Iguma, (International Journal of Scientific Research in Science and Technology, 2024)
The integration of Big Data Analytics and Artificial Intelligence (AI) in healthcare is revolutionizing diagnostics, treatment, and disease prevention. This paper explores how these advanced technologies enhance clinical decision-making, improve patient outcomes, and optimize healthcare processes. By leveraging vast datasets, AI-driven algorithms facilitate early disease detection, predictive analytics, and personalized medicine, significantly reducing diagnostic errors and enabling timely interventions. Furthermore, machine learning models assist in tailoring treatment plans based on patient-specific data, leading to more effective and efficient therapeutic strategies. In disease prevention, big data analytics enable epidemiological surveillance, tracking disease patterns, and identifying at-risk populations. AI-powered predictive models support proactive interventions, reducing the burden of chronic illnesses and infectious diseases. The paper highlights key advancements in AI applications, including deep learning in medical imaging, natural language processing in electronic health records, and real-time analytics in wearable health devices. Despite these transformative benefits, challenges such as data privacy, ethical concerns, and integration complexities remain barriers to widespread adoption. The study concludes that while AI and big data analytics hold immense potential to reshape healthcare, addressing regulatory, infrastructural, and ethical considerations is crucial for sustainable implementation. By fostering interdisciplinary collaboration and robust policy frameworks, healthcare systems can harness these technologies to drive innovation, enhance efficiency, and improve global health outcomes.
Keywords: Big Data Analytics; Artificial Intelligence; Healthcare; Diagnostics; Treatment; Disease Prevention